Post-bubble blues : how Japan responded to asset price collapse - Collyns, Charles; Bayoumi, Tamim A. (Washington, D.C. : International Monetary Fund, 2000)
This book presents a compelling story about Japan's economy. It examines the causes of the lingering economic problems of Japan, the crisis in its banking system, the reasons for weak business investment, and the government's efforts to kick-start the economy through a series of stimulus package.
Includes bibliographical references.
rua 09/03/15
Loans
Keywords: Financial crises -- Japan; Stocks -- Prices -- Japan; Monetary policy -- Japan; Japan -- Economic conditions -- 1989-